The effect of exercise self-efficacy on exercise participation among Chinese university students: chain mediation of interest in sport learning and procrastination behavior - Yong, Jiang; Fan, Wu (Frontiers in Psychology, 2025)
PurposeTo investigate the mediating role of sports learning interest and procrastination behavior between exercise self-efficacy and exercise participation among college students.MethodsA questionnaire survey was conducted with 500 Chinese university students using the Physical Activity Rating Scale (PARS-3), the Exercise Self-Efficacy Scale, the Sport Learning Interest Scale, and the Procrastination Behavior Scale.ResultsPearson correlation analysis showed that exercise self-efficacy, interest in sport learning, procrastination behavior and exercise participation were correlated with each other. The results of path analysis indicated that exercise self-efficacy was not a significant direct predictor of exercise participation. The results of mediation effects analysis indicated that sport learning interest and procrastination behavior fully mediated the relationship between exercise self-efficacy and exercise participation; the chain mediation effect of sport learning interest and procrastination behavior was significant. There were both separate mediating effects of sport learning interest and procrastination behavior between exercise self-efficacy and exercise participation, and a chain mediating effect that influenced procrastination behavior through sport learning interest, which in turn influenced exercise participation.ConclusionIncreased exercise self-efficacy promotes individual interest in sport learning, which leads to a decrease in procrastination and an increase in exercise participation.